Associations of C-Reactive Protein to Indices of Vascular Health and the Influence of Serum 25(OH)D Status in Healthy Adults - Ambika P. Ashraf; Gordon Fisher; Jessica Alvarez; Tanja Dudenbostel; David A. Calhoun; Alexander J. Szalai; Barbara A. Gower (Journal of Nutrition and Metabolism)
Elevated serum high-sensitivity C-reactive protein (hs-CRP) and low serum 25-hydroxyvitamin D [25(OH)D] are associated with increased cardiovascular disease (CVD) risk. Ethnic differences in serum hs-CRP and 25(OH)D concentrations and CVD are known. Objectives: to investigate the ethnic differences in hs-CRP concentrations, to assess the influence of 25(OH)D on these ethnic differences and to examine the influence of 25(OH)D on association between hs-CRP and cardiovascular health indices. Subjects: 62 healthy adults [26 African Americans (AA), 26 European Americans (EA), and 10 Hispanic Americans (HA)], ages 18–55 years. Serum hs-CRP and 25(OH)D as well as pulse wave velocity (PWV), augmentation index (AIx), and flow-mediated dilatation (FMD) were measured. hs-CRP was inversely associated with 25(OH)D (r=−0.25, P=0.049), and hs-CRP was positively associated with PWV (r=0.29, P=0.04). The association of hs-CRP with PWV attenuated after adjustment for 25(OH)D (P=0.15). hs-CRP was higher in AA compared to EA (P=0.05); this differences was reduced by 32% after adjusting for serum 25(OH)D. Conclusion: eventhough the inverse association between serum 25(OH)D and CRP does not infer causality, lower serum 25(OH)D may increase risk for inflammation and endothelial dysfunction. The lower 25(OH)D in AA may predispose to greater inflammation and associated vascular dysfunction.